Antioxidant activity of bioactive peptide derived from Pekin duck feet gelatin hydrolysate - Fatin Arina Mohd Zain,; Norshazila Shahidan,; Nurul Huda,; Zarinah Zakaria,; Septama, Abdi Wira (Penerbit Universiti Kebangsaan Malaysia, 2020)
Malaysia is one of the main producers of duck meat globally with increasing demands. Increasing in duck production will also increase the number of duck by-products such as skin, feet and bones. Pekin duck (Anas platyrhyncos domestica) is one of the famous duck breeds. Gelatin that was extracted from Pekin duck feet has shown a potential raw material for the production of bioactive peptide that can involve in various functions of the organism physiologically for example antioxidant effects. Pekin Duck feet gelatin was hydrolyzed by using five commercial enzymes (Alcalase, Esperase, Flavourzyme, Neutrase and Protamex) to identify radical scavenging potencies of derived bioactive peptides. All the five enzymes were studied under three different enzyme-substrate ratio (1:10, 1:15, 1:20) with every enzyme optimum pH and temperature. Scavenging activities studied included DPPH radical scavenging activity and ABTS radical scavenging activity. In DPPH radical scavenging activity, all the five enzymes showed the highest percentage of radical scavenging activity at (1:20) enzyme-substrate ratio condition. Among the five enzymes studied, gelatin hydrolyzed with Protamex showed the highest activity (54.83%), followed by Alcalase (53.12%), Esperase (49.81%), Flavourzyme (49.32%) and lastly Neutrase (47.49%) at sample concentration 4.5 mg/ml. The half-maximal inhibitory concentration (IC50) value of the bioactive peptide for ABTS radical scavenging activity was measured. Alcalase has produced the duck feet gelatin hydrolysate that has the lowest IC50 value against ABTS radical scavenging activity with value (0.45%) followed by Esperase (0.54%), Neutrase (0.57%), Protamex (0.60%) and lastly Flavourzyme (0.74%).